Is dosing time important for treating hypertension?. Issue 5 (5th March 2015) - MacDonald, Tom
<x xml:space="preserve">Abstract</x> The TIME study aims to investigate the importance of time of dosing in treating hypertension and reducing the risk of cardiovascular events. Here, Professor Tom MacDonald discusses how the trial will be conducted, patient eligibility and how GP practices can aid recruitment.